2020
DOI: 10.31364/scirj/v8.i8.2020.p0820800
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Leadership and Organizational Commitment to Organizational Citizenship Behavior and Work Achievement

Abstract: This study aims to examine the effect of leadership and organizational commitment on organizational citizenship behavior (OCB) and work performance in civil servants of sports coach formations in the Bali Provincial Government. The population in this study were all civil servants who were appointed to the sports coach formation in the Bali Provincial Government, totaling 32 people. Data relating to research variables were collected using a questionnaire that was distributed to all respondents and filled in by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Thus, the potential of a region should be utilized through community empowerment to improve the community's economy. When the citizens are empowered, their ability to develop is enhanced (Yuesti & Sumantra, 2017). The process of implementing knowledge management strategies includes procedures for creating, storing, disseminating, and applying knowledge.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the potential of a region should be utilized through community empowerment to improve the community's economy. When the citizens are empowered, their ability to develop is enhanced (Yuesti & Sumantra, 2017). The process of implementing knowledge management strategies includes procedures for creating, storing, disseminating, and applying knowledge.…”
Section: Review Of Extant Literaturementioning
confidence: 99%
“…Evidence in extant literature affirms a positive relationship between knowledge management and economic development (Abubakar et al, 2019;Holsapple & Joshi, 2000;Jarboe, 2001;Yuesti & Sumantra, 2017). When information on development is disseminated and knowledge shared with the right audience and leveraging the suitable medium, it leads to empowerment.…”
Section: The Place Of Knowledge Management In Economic Developmentmentioning
confidence: 99%
“…On the other hand, there is also research that finds contradictory results, such as (Pramesty et al, 2020) finding that organizational commitment has no significant effect on organizational citizenship behavior and performance. Then Abdullahi (2020) also found that the role of leadership behavior cannot influence the creation of organizational citizenship behavior.…”
Section: Which Suggests Organizational Citizenshipmentioning
confidence: 99%
“…Sholikhah & Prastiwi, (2020) also state the same thing that there is a positive and significant influence between organizational commitment on organizational citizenship behavior. Based on this, the hypothesis in this study can be formulated as follows:H1: Organizational commitment has a positive and significant effect on organizational citizenship behaviorMowday et al, (1982) inCobbinah et al, (2020);Desky et al, (2020);Donkor et al, (2021); Grego-Planer, (2019);Sholikhah & Prastiwi, (2020);and Pramesty et al, (2020)…”
mentioning
confidence: 97%
See 1 more Smart Citation